Prospects for digital transformation of the monetary systems - O. I. Larina; N. V. Moryzhenkova (Вестник университета)
The active digitalization of financial markets generates new types of digital financial assets, and also raises questions about prospects of the national monetary systems development, taking into account the emerging digital financial instruments. The authors present the results of a study conducted via interviewing respondents about their attitude to cryptocurrencies, about the likelihood of cashless economies, and about the impact of economy digitalization on changing people’s lives. Current scientific studies show that a significant part of authors is inclined to believe that current digitalization trends will lead to the complete disappearance of cash, including cryptocurrencies will play an important role in this process. Low financial literacy, possible failures in electronic payment systems, the difficulty of adaptation for certain groups of the population are the reasons that delay the transition to cashless economies. However, a significant number of advantages that digital assets provide for the development of the economy, and the positive attitude of society to the changes taking place in the process of digital transformation, contribute to a further change in the monetary system.